Creativity - as a motivating factor in teaching in pedagogical universities - Nazarova, Barno A. (International Journal of Psychosocial Rehabilitation, 2020)
This article summarizes the data on the very problem of creativity, the creativity of the individual, on research on this topic, on the components of the very concept of creativity. The characteristic of creativity as the ability to create is given. The significance of the research, the initial positions of the mutual influence of various influences is substantiated. defining the concept of creativity. The main theoretical approaches to the study of the nature and structure of creativity for the development of its development strategy are analyzed.